تطوير طريقة القواعد والترجمة لترجمة كتب التراث :بحث تطويرم في مادة قراءة الكتب في قسم التًبية الإسلامية بجامعة سوناف غونونج جاتي الإسلامية الحكومية باندكنج - Dedih wahyudin (Jurnal Pendidikan Islam, 2015)
The research is based on the fact that many students are still weak in reading kutub at-turāts, weak in signing harakat and wrong in translation. It is caused by implementing Grammar Translation Method which doesn’t lead the student to have the equal competence between reading and translating the Arabic texts. The objective of this research is to find a model of the development of grammar and translation method in teaching Qirā’atul Kutub to translate the kutub at-turāts and testing its effectiveness. The theoretical framework underlying the development of grammar translation method is the structuralism theory and constructivism theory. This study uses research and development (R & D). The steps are: (1) Preliminary  Research, (2) The Development of Grammar Translation Method, (3) testing the developed method, and (4) validation of the developed method. The techniques of collecting data in this study are observation, questionnaires, interviews and test. The results showed that the developed Grammar Translation Method can improve the quality of reading and translating kutub at-turāts both in terms of process and outcome.